Ledipasvir/sofosbuvir for treatment of hepatitis C virus in sofosbuvir‐experienced, NS5A treatment‐naïve patients: Findings from two randomized trials. (5th December 2017) - Tam, Edward; Luetkemeyer, Anne F.; Mantry, Parvez S.; Satapathy, Sanjaya K.; Ghali, Peter; Kang, Minhee; Haubrich, Richard; Shen, Xianlin; Ni, Liyun; Camus, Gregory; Copans, Amanda; Rossaro, Lorenzo; et al.
Abstract: Background & Aims: We report data from two similarly designed studies that evaluated the efficacy, safety, and optimal duration of ledipasvir/sofosbuvir (LDV/SOF) ± ribavirin (RBV) for retreatment of chronic hepatitis C virus (HCV) in individuals who failed to achieve sustained virological response (SVR) with prior SOF‐based, non‐NS5A inhibitor‐containing regimens. Methods: The RESCUE study enrolled HCV mono‐infected adults with genotype (GT) 1 or 4. Non‐cirrhotic participants were randomized to 12 weeks of LDV/SOF or LDV/SOF + RBV. Compensated cirrhotic participants were randomized to LDV/SOF + RBV (12 weeks) or LDV/SOF (24 weeks). The AIDS Clinical Trials Group A5348 study randomized genotype 1 adults with HCV/HIV co‐infection to LDV/SOF + RBV (12 weeks) or LDV/SOF (24 weeks). Both studies used SVR at 12 weeks post‐treatment (SVR12) as the primary endpoint. Results: In the RESCUE study, 82 participants were randomized and treated, and all completed treatment. Overall, SVR12 was 88% (72/82); 81‐100% in non‐cirrhotic participants treated with LDV/SOF or LDV/SOF + RBV for 12 weeks and 80‐92% in cirrhotic participants treated with LDV/SOF + RBV for 12 weeks or LDV/SOF for 24 weeks. Adverse events (AEs), mostly mild‐to‐moderate in severity, were experienced by 78% of participants, with headache and fatigue most frequently reported. One serious AE, not related to treatment, was observed. No premature discontinuations of study drug, or deaths occurred. In the A5348 study, seven participants were randomized (cirrhotic n = 1; GT1a n = 5) and all attained SVR12, with no serious AEs or premature discontinuations. Conclusions: In this SOF‐experienced, NS5A inhibitor‐naïve population, which included participants with cirrhosis or HCV/HIV co‐infection, high SVR12 rates were achieved.